Preparation of TiO2 Thin Films by Potentiostatic Method: The Effects of Electrode Potential and Electrodeposition Temperature - Wu, Shibiao; Xu, Ling; Xu, Haiyan; Li, Feifei; Jin, Jie; Yao, Qiushi; Wang, Yuan; Hong, Dekai (Asian Journal of Chemistry, 2013)
White films were electrodeposited by potentiostatic method on the indium tin oxide conductive glass substrate. After annealing at 450 ºC for 1 h, the films were characterized by XRD and SEM. According to the XRD patterns, the annealed films proved to be TiO2 with anatase phase structure. The effects of the experimental parameters such as electrodeposition potential and temperature on formation of the deposited films were discussed. The optimal electrode potential and desirable electrodeposition temperature were 1 V and 30 ºC, respectively.